2013
DOI: 10.1039/c3ra41079j
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-doped graphene nanosheets as efficient metal-free oxygen reduction electrocatalysts

Abstract: Metal-free phosphorus-doped graphene nanosheets (P-TRG) with large surface area (496.67 m 2 g 21 ) and relatively high P-doping level (1.16 at.%) were successfully prepared by thermal annealing a homogenous mixture of graphene oxide and 1-butyl-3-methlyimidazolium hexafluorophosphate under argon atmosphere. It was found that the P atoms were substitutionally incorporated into the carbon framework and were partially oxidized, which created new active sites for the oxygen reduction reaction (ORR).Accordingly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
240
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(252 citation statements)
references
References 55 publications
(36 reference statements)
4
240
0
2
Order By: Relevance
“…In 2013, the metal-free P-doped graphene nanosheets were successfully synthesized by thermal annealing of the mixture GO and an ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim]PF6), which was employed as a mild phosphorus source for in situ doping the thermally reduced GO (TRG) (Figure 15g-l) [79]. The morphology is further evidenced by TEM as shown in Figure 15g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, the metal-free P-doped graphene nanosheets were successfully synthesized by thermal annealing of the mixture GO and an ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim]PF6), which was employed as a mild phosphorus source for in situ doping the thermally reduced GO (TRG) (Figure 15g-l) [79]. The morphology is further evidenced by TEM as shown in Figure 15g.…”
Section: Introductionmentioning
confidence: 99%
“…Substitutional doping with B, phosphorus (P), N, or sulfur (S) single atoms in the carbon network could modulate the chemical characteristics, create new active sites, and greatly improve the catalytic activity of graphene [27,33,37,43,[77][78][79][80]. In particular, co-doping through the mixture of two or three metal elements with electronegativity could produce a novel electron distribution resulted in a synergistic effect [86].…”
Section: Introductionmentioning
confidence: 99%
“…One of the possibilities to enhance the hydrogen storage capacity in graphene material is to incorporate an active site on a graphene that is to substitute carbon atom by another element. The doping elements include N and B, however doping with P and S have also been reported [33]- [44]. It has been proposed that heteroatom might be the alternate active centers for hydrogen activation and this activated hydrogen might move to the carbon surface by spill over [45].…”
Section: Introductionmentioning
confidence: 99%
“…50 Li et al reported metal-free P-doped graphene nanosheets by annealing a homogeneous mixture of graphene oxide and an ionic liquid (BmimPF 6 ), as shown in Figure 10. 51 P atoms in the as-prepared PG are partially oxidized and existed as tetrahedral forms such as C 3 PO, C 2 PO 2 , and CPO 3 . The O atom with the higher electronegativity will first make the P atom polarized, and then withdraw electrons from the carbon atoms with the polarized P atom as a bridge, creating a net positive charge on the carbon atoms adjacent to the P atom.…”
Section: Phosphorus-doped Graphenementioning
confidence: 99%